Experimental Study on Early Polymer Injection Timing of Heavy Oil Reservoir in Bohai Sea - Zhu, Shijie; Xue, Zeng; Wang, Rui; Fu, Lei; Tu, Zhiyuan; Su, Jiachun; Shi, Leiting (Journal of Basic & Applied Sciences, 2022)
The polymer flooding of ordinary heavy oil reservoirs in Bohai Sea can improve the crude oil recovery by advancing the injection time of polymer flooding. The better the injection time is, the higher the enhanced recovery is, and the greater the income is. Based on Bohai Oilfield, the polymer application system was characterized in the laboratory, and then polymer flooding experiments were carried out at different times using one-dimensional core model. The results show that: 1) polymer AP-P4 can establish good mobility control ability (RF=107, RRF=28.5) under the target reservoir conditions; 2) Under the experimental conditions, the best time for polymer injection is to switch to polymer injection after 0.203PV water injection, and the oil recovery can be increased by 27.73%. Early polymer injection technology is very beneficial to polymer flooding in offshore oil fields.